2013
DOI: 10.1111/apa.12483
|View full text |Cite
|
Sign up to set email alerts
|

Late development of complete atrioventricular block may be immune mediated and congenital in origin

Abstract: Our observations support the hypothesis that late progression to CAVB can be the result of an immune-mediated pathogenetic mechanism during foetal life. An autoantibody-associated diagnosis after the neonatal period is therefore possible, and testing of maternal serology at the time of diagnosis is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, a recent report from the Swedish cardiac NL cohort identified 13 anti-SSA/Ro-exposed cases diagnosed after birth (age 4 months to 43 years of age), 11 with normal heart rates in utero (42). These findings support the hypothesis that immune-mediated inflammation and fibrosis in cardiac tissues can continue postnatally, resulting in late progression to cardiac NL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent report from the Swedish cardiac NL cohort identified 13 anti-SSA/Ro-exposed cases diagnosed after birth (age 4 months to 43 years of age), 11 with normal heart rates in utero (42). These findings support the hypothesis that immune-mediated inflammation and fibrosis in cardiac tissues can continue postnatally, resulting in late progression to cardiac NL.…”
Section: Discussionmentioning
confidence: 99%
“…26 Starting with this body of evidence, in a Swedish nationwide retrospective study, 53 cases of isolated III1AVB of unknown origin were identified in whom the diagnosis was made after the cutoff period of 27 days of life (range 4 months-43 years, median 9 years, mean 13.6 years) and whose mothers were available for blood sampling. 29 Among these cases, 13 (24.5%) had a seropositive mother. All these 13 subjects were anti-Ro/SSA-negative.…”
Section: Late Progressive Congenital Formmentioning
confidence: 99%
“…In the Swedish nationwide retrospective study, 2 of 13 reported cases were diagnosed in relation to infections, suggesting that microbes may be a triggering factor. 29 In the other patients who had no evident pathogenic factor other than maternal autoantibodies, milder infections cannot be excluded. Moreover, 1 subject had a family history of cardiomyopathy, which may have contributed to the late progression of the conduction defect.…”
Section: Putative Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, maternal autoantibodies have been detected in only a minority of children, in whom AV block was diagnosed beyond the neonatal period, a different, distinct clinical entity [15, 34, 95]. However, some isolated AV blocks diagnosed beyond the neonatal period are also immune-mediated, even with late detection of maternal anti-Ro/SSA autoantibodies [12]. This condition, emerging in childhood or even in the adult age, represents a late progressive congenital form of immune AV block with the late development of a subclinical anti-Ro/SSA-induced congenital damage of the conduction system, related to a not fully understood autoantibody-independent worsening with age [51].…”
Section: Atrioventricular Conduction Disorders In Structurally Normalmentioning
confidence: 99%